UTILISATION OF DIARY TO DEVELOP WRITING SKILLS OF GRADE 2 STUDENTS - Sandra, Mutia Mei; Mustika, Dea (JMIE (Journal of Madrasah Ibtidaiyah Education), 2024)
It is known that grade 2 students have not mastered the initial writing skills, which are influenced by the lack of interest and minimal talent of students in writing. This study aims to describe the use of diaries in developing the initial writing skills of grade 2 students of SDN 007 Kampung Baru Cerenti. The research method used in this study is qualitative with a verification research type. The researcher used data collection techniques through observation, interviews and documentation involving subjects, namely teachers and grade 2 students of SDN 007 Kampung Baru Cerenti. The data analysis technique in this study used the Miles and Huberman model, which consisted of data reduction, data presentation, and conclusion. Based on the results of the survey show that there are three approaches used to determine the use of diaries in developing the initial writing skills of grade 2 students of SDN 007 Kampung Baru Cerenti, namely by using diaries and grouping them according to the level of student ability and by motivating students to learn to improve their writing skills. This study implies that it can help grade 2 students improve their writing skills by composing sentences with the correct writing structure.